Qianggu concentrate: unlocking bone protection power via antioxidative SIRT1/NRF2/HO-1 pathways in type 2 diabetic osteoporosis - Wang, Kaili; Dang, Xiang; Wang, Yanyan; Yang, Qing; Zhang, Tingting; Yang, Peng; Yuan, Ling; Xu, Rongming; Dang, Yuqi; Nan, Yi (Frontiers in Pharmacology, 2024)
Background: Qianggu Concentrate (QGHJ), a traditional Chinese medicine, is extensively used to treat Type 2 Diabetic Osteoporosis (T2DOP). Despite its widespread use, research on its therapeutic mechanisms within T2DOP is notably scarce. Objective: to explore QGHJ's osteoprotection in T2DOP rats and BMSCs, focusing on the antioxidant activation of SIRT1/NRF2/HO-1 and NRF2 nuclear migration. Methods: QGHJ constituent analysis was performed using UPLC-HRMS. Safety, bone-health efficacy, and glucose metabolic effects in T2DOP rats were evaluated via general condition assessments, biomarker profiling, micro-CT, biomechanics, staining methods, and ELISA, supplemented by RT-PCR and Western blot. BMSCs' responses to QGHJ under oxidative stress, including viability, apoptosis, and osteogenic differentiation, were determined using CCK-8, flow cytometry, ALP/ARS staining, and molecular techniques. The modulation of the SIRT1/NRF2/HO-1 pathway by QGHJ was explored through oxidative stress biomarkers, immunofluorescence, and Western blot assays. Results: UPLC-HRMS identified flavonoids, monoterpenes, and isoflavones as QGHJ's key compounds. In vivo, QGHJ proved safe and effective for T2DOP rats, enhancing bone mineral density, microenvironment, and biomechanical properties without impairing vital organs. It modulated bone markers PINP, TRACP 5b, RUNX2 and PPARγ, favoring bone anabolism and reduced catabolism, thus optimizing bone integrity. QGHJ also regulated glycemia and mitigated insulin resistance. In vitro, it preserved BMSCs' viability amidst oxidative stress, curbed apoptosis, and fostered osteogenesis with regulated RUNX2/PPARγ expression. Mechanistic insights revealed QGHJ activated the SIRT1/NRF2/HO-1 pathway, augmented NRF2 nuclear translocation, and enhanced the antioxidative response, promoting bone health under stress. Conclusion: In T2DOP rat and BMSCs oxidative stress models, QGHJ's bone protection is anchored in its antioxidative mechanisms via the SIRT1/NRF2/HO-1 pathway activation and NRF2 nuclear translocation.